Christmas gifts for Spain (leaflet) (1938)
032-0002-005 CHRISTMAS CARDS Many people who wish to send a Christmas parcel to a friend in Spain, or make a Christmas Gift to our Spanish friends in other ways, may be obliged to economise on their usual Christmas gifts, and disappoint many friends at home. We can assist you to find a way out of this dilemma. You may send to those friends a Christmas Card explaining that this Christmas you are sending your Christmas Gifts to Spain. This Christmas Card is illustrated by LOW, with a verse by ELEANOR FARJEON, "STANDARD PARCEL" SERVICE TO SPAIN Type No. 1A 6/- Total weight, 17 lbs. 2 tins Condensed Milk 4½ lbs. Soap 1 lb. 2 oz. Lard 2¼ lbs. Beans 20 Soup Cubes 2¼ lbs. Sugar 1 tin Meat 2¼ lbs. Codfish 9 ozs. Soup Paste Type No. 1B 6/- Total weight, 20¼ lbs. 6¾ lbs. White Beans 6¾ lbs. Soap 2¼ lbs. Lard 4½ lbs. Codfish Type No. 2A 12/- Total weight, 31½ lbs. 4 tins Condensed Milk 6¾ lbs. Soap 4½ lbs. Sugar 1 lb. 2 oz. Coffee 4½ lbs. Rice 2¼ lbs. Soup Paste 1 lb. 2 oz. tin of Jam 2¼ lbs. Chocolate 2¼ lbs. Codfish 2¼ lbs. Lard Type No. 2B 12/- Total weight, 31½ lbs. 6 tins Condensed Milk 11¼ lbs. Soap 2¼ lbs. Coffee 6¾ lbs. Sugar 4½ lbs. Codfish Type No. 3A 24/- Total weight, 40½ lbs. 6 tins Condensed Milk 9 lbs. Soap 2¼ lbs. Coffee 4½ lbs. Sugar 2 tins Meat 6¾ lbs. Rice 2¼ lbs. Lard 2 tins Jam 2¼ lbs. Chocolate 2¼ lbs. Cocoa 2¼ lbs. Codfish 2¼ lbs. Salami 2¼ lbs. Soup Paste 20 Soup Cubes 1 lb. 2 oz. tinned Salmon 6 tins Sardines Type No. 3B 24/- Total weight, 69¾ lbs. 6 tins Condensed Milk 11¼ lbs. Sugar 11¼ lbs. Rice 11¼ lbs. White Beans 4½ lbs. Coffee 11¼ lbs. Codfish 2¼ lbs. Lard 11¼ lbs. Soap Type No. 4 (Special for Children) Price 20/-Total weight, 20¼ lbs. 4 tins Milk Powder 4½ lbs. Sugar 1 box Vitamin Marzipan 2 tins Jam 2 tins Flour 1 Parcel Biscuits Type No. 5 (Special for diabetic patients) Price 20/- Total weight, 18 lbs. 6¾ lbs. Cheese 3 tins Preserved Fish 2 tins Dextrinated Flour 2¼ lbs. Unsweetened Milk Powder Printed by the VICTORIA HOUSE PTG. CO. Ltd. (T.U. all Depts.), 55 and 57 Drury Lane, London, W.C.2 292/946/32/2(iv)